ANTIOXIDANT ACTIVITY OF ETHANOLIC EXTRACT AND n-HEXANE FRACTION FROM SIKKAM (Bischofia javanica BLUME) STEM BARK - Jambak, Kadriyani; Nainggolan, Marline; Dalimunthe, Aminah (Asian Journal of Pharmaceutical Research and Development, 2019)
Objectives: The current investigation was conducted to examine the secondary metabolites content of sikkam (Bischofia javanica BLUME) stem bark. Antioxidant activity of the ethanolic extract and n-hexane fraction of sikkam stem bark were also evaluated. Design: The design of this study was quantitative experimental, where quantitative antioxidant activity was tested by using the DPPH radical scavaging method and measured using a UV-Vis spectrophotometer. Interventions: the variable that was intervened in this study was the concentration of extract used. Main outcome measures: The main measurement carried out in this study is the absorbance value of DPPH which is converted into a 50 inhibitory concentration value (IC50). Results: Simplicia and ethanolic extract of sikkam stem bark exhibited secondary metabolites content of flavonoids, glycosides, tannins and triterpenoids. Ethanolic extract of sikkam stem bark (EESSB) and n-hexane fraction of sikkam stem bark (NHFSSB), exhibited very strong antioxidant activity with an IC50 of 12,248 µg/mL and 39,622 µg/mL. Conclusion: The sikkam stem bark had contained flavonoids, glycosides, tannins, triterpenoid, and had a very strong antioxidant activity, where EESSB had a stronger activity than NHFSSB. Keywords: Bischofia javanica, stem bark, antioxidant, secondary metabolites